Program Kuliah Kerja Nyata Universitas Gadjah Mada, 1970-an – 2000-an: Kebijakan, Bentuk, dan Perdebatan Pemikiran - Suwignyo, Agus; Sudarmadi, Tular; Wahyuni, Hermin Indah (Department of History, Faculty of Humanities, Diponegoro University, 2024)
The Student’s Community Service (Kuliah Kerja Nyata, KKN) has become a hallmark of higher education in Indonesia. Nonetheless, the history and intricacies of the implementation of this program have been overlooked in scholarly studies. The aim of the present article was to analyze the policies, forms and debates on KKN program from the 1970s to 2000s. This article was focused on the KKN program that was carried by the university that first initiated it in Indonesia, namely Gadjah Mada University. As a pioneer, UGM has the experiences in and the most complete archival collection about the KKN program among public and private universities in Indonesia. By applying the historical method and using KKN UGM reports from the 1970s–2000s as data sources, this article argues that, along the time of its existence, the KKN program at UGM has faced ups and downs as well as pros and cons. The article shows that the policies and the forms of the KKN program continue to adapt to the current context. Its contents, target community groups, and models of evaluation are increasingly varied and established from time to time. However, the principles and ideas that underline the program are also dynamic, especially regarding its impact and relevance in a modernizingsociety.